ANALISIS PENGARUH PELATIHAN DAN PROMOSI TERHADAP PRESTASI KERJA PADA DINAS PERTANIAN DAN PETERNAKAN KABUPATEN PINRANG - Sitti Mujahida Baharuddin; Warka Syachbrani (P3M STIEM BONGAYA, 2019)
This study aims to analyze and describe the effect of training and promotion on workperformance. This research is an explanatory research. In this study, the population is all of theEmployees of the Agriculture and Animal Husbandry Office of Pinrang Regency, amounting to57 people. The results showed that training had a positive and significant effect on workperformance and positive and significant promotions on employee performance. Workperformance has a positive and significant effect on training and promotion